Global Marketing Plan and Strategy of PT Sumber Daya Energi Coal Mine Under China Qinfa Group - Chen Xiaoli; Gallang Perdhana Dalimunthe (Cakrawala Repositori IMWI)
The global coal industry is undergoing significant transformation due to energy transition policies, environmental regulations, geopolitical uncertainties, and fluctuations in commodity prices. Although coal demand has declined in some developed countries, Asian markets—particularly China, India, and Vietnam—continue to present substantial opportunities. PT Sumber Daya Energi (SDE) Coal Mine, a strategic mining project under China Qinfa Group, has significant production capacity and integrated infrastructure; however, it faces challenges in global market penetration, brand recognition, product acceptance, buyer confidence, and sustainable competitiveness. This study aimed to formulate an effective global marketing strategy for SDE Coal Mine to strengthen its international market position and support long-term business growth.This research employed a qualitative case study approach by integrating industry analysis, interview insights, pattern matching, SWOT analysis, and a multi-criteria decision-making approach using AHP and EDAS. The findings revealed that market size, price attractiveness, product compatibility, and relationship potential were the most influential factors in selecting export markets. The AHP-EDAS analysis identified China, South Korea, and Vietnam as the most attractive markets. Considering current production capabilities and product specifications, China, India, and Vietnam were prioritized as the main target markets. The proposed global marketing strategy consisted of five key areas: product differentiation, market-based pricing, distribution optimization, relationship-oriented promotion, and strategic partnership development.